OPTIMIZATION OF SURGICAL TREATMENT OF EARLY DEEP BURN - Daminov Feruz Asadullayevich; Saydullayev Zayniddin Yakshiboyevich; Xursanov Yoqubjon Erkin ugli; Rustamov Inoyatulla Muradullayevich (Research Focus International Scientific Journal, 2023)
An analysis was made of the management of patients with dermal burns in a specialized department, taking into account the choice of the method of wound management: conservative and early surgical restoration of the skin.